Peasant Women Weaving Food Sovereignty Networks in Syndemic Times - Thelma Mendes Pontes; Gisela Illescas; Monica Hernandez; Denisse Garcia; Irma Calte; Juliana Merçon; Citlalli Binnqüist (Universidade Federal do Norte do Tocantins, 2023)
The COVID-19 pandemic must be analyzed as a syndemic, resulting from the interaction between diseases and political and socioeconomic macro-processes that affect food sovereignty, mainly of women. The peasant movements propose, as a way out of the multi-crises, the transformation of the food system, based on food sovereignty and feminist principles. In this article, we use data from a transdisciplinary investigation and a report produced by women to guide actions in relation to gender issues, COVID-19 and food systems, as a basis for the analysis of a particular case in Mexico: the initiatives carried out to confront the COVID-19 syndemic by coffee-growing women, peasant and popular feminists, in two communities in the mountains of Veracruz. The objective of this article is to demonstrate that these women have managed to strengthen the bonds of solidarity in their communities, of reciprocity with Mother Earth and comprehensive health care through the strengthening of ancestral practices (plant gathering and barter), and new tools (self-care circles and digital media). This article demonstrates how the ways of life of these women, their creativity and resilience materialize locally, and thus proposes the construction of another narrative by and about peasant women.